2015
DOI: 10.1186/s12879-015-1129-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B virus infection among health care workers in a tertiary hospital in Tanzania

Abstract: BackgroundSub-Saharan Africa has a high prevalence of hepatitis B virus (HBV) infections. Health care workers (HCWs) are at high risk of contracting HBV infection through their occupation. Vaccination of HCWs against HBV is standard practice in many countries, but is often not implemented in resource-poor settings. We aimed with this cross-sectional study to determine HBV prevalence, HCW vaccination status, and the risk factors for HCWs contracting HBV infection in Tanzania.MethodsWe enrolled 600 HCWs from a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
88
4
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(110 citation statements)
references
References 23 publications
14
88
4
4
Order By: Relevance
“…These data corroborate others from tertiary hospitals in Tanzania and Uganda, which also found remarkably high prevalence of HBsAg positivity in HCWs, at 7.0% and 8.1% respectively. 25 Our findings are also comparable to estimates in other high-risk groups in Cameroon. Frambo et al reported a prevalence of 9.7% among pregnant women, and Noubiap et al reported a prevalence of 10.1% in blood donors.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These data corroborate others from tertiary hospitals in Tanzania and Uganda, which also found remarkably high prevalence of HBsAg positivity in HCWs, at 7.0% and 8.1% respectively. 25 Our findings are also comparable to estimates in other high-risk groups in Cameroon. Frambo et al reported a prevalence of 9.7% among pregnant women, and Noubiap et al reported a prevalence of 10.1% in blood donors.…”
Section: Discussionsupporting
confidence: 88%
“…More than 2 billion people have been infected with Hepatitis B virus (HBV) globally, and 240 million are chronic carriers of the disease. 1,2 Africa is considered to be endemic for HBV; and the disease is hyperendemic in Cameroon where prevalence has been estimated at 11.9%. 3,4 Healthcare workers (HCWs) are one of the most vulnerable groups to HBV infection from occupational exposures, with up to four times greater risk of contracting the infection than the general population.…”
Section: Introductionmentioning
confidence: 99%
“…This could partly be explained due to high prevalence of viral hepatitis B infection in the younger adults which is among the commonest causes of acute and chronic liver failure to both the general and health care worker populations in Tanzania [12,13]. The male predominant population in this study is likely due to the risk of chronic alcohol use as a cause of liver disease which was consistent with other studies [11].…”
Section: Discussionsupporting
confidence: 87%
“…They are considered as one of World Health Organization (WHO) public health priority after the HIV infection, malaria and tuberculosis [2,3]. Worldwide, it is estimated that more than 2 billion people and 170 million people are infected with hepatitis B virus (HBV) and hepatitis C virus (HCV) respectively with 3 -4 million new infections occurring each year [4,5]. The prevalence of HB and HC is highest in subSaharan Africa and East Asia, with an estimated 5-10% adults with chronic infection [2].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of HB and HC is highest in subSaharan Africa and East Asia, with an estimated 5-10% adults with chronic infection [2]. Of these, 240 million people are chronic carriers of HBV and are at risk of death from acute fulminant liver disease, hepatocellular carcinoma (HCC) or liver cirrhosis [5,6]. In Cameroon the prevalence of HBV ranges from 6.3-11.5% [7] while the range of HCV is 6.9% -56.0% [8][9][10].…”
Section: Introductionmentioning
confidence: 99%